Acinic cell carcinoma arising in mucosal surface of upper lip : A case report and A review of the literature - Miyata, Masaru; Utsumi, Nobuo; Miyamoto, Hizuru; Kurumaya, Hiroshi; Sakashita, Hideaki (Journal of Japanese Society of Oral Oncology, 1991)
Acinic cell carcinoma is an uncommon neoplasm of the salivary glands, accounting for approximately 2-4% of all parotid gland tumor. Their occurrence in minor salivary gland site is exceedingly rare. A case of acinic cell carcinoma arising in mucosal surface of upper lip was reported, and a review of literature was briefly carried out. A 44-year-old man was referred to our department, with a painless swelling on the right side of the upper lip. There was no regional lymphadenopathy. At the first examination, the tumor appeared as a mass of about 20×20mm in size, which was histopathologically diagnosed as acinic cell carcinoma. Under the general anesthesia, the tumor was resected with radical excision by intra-oral approach and reconstructed with splint thickness skin graft. No recurrence or metastasis has been observed after the operation. we surveyed 54 cases of this tumor of the minor salivary gland in Japanese literature during the period 1955 to 1991. In these reports, the tumor occurred most frequently in palate (19 cases), followed by retromolar region (9 cases), lip (7 cases), buccal mucosa (7 cases), and others (12 cases) . The tumor yielded a recurrence rate of 21.6 % in the literatures.